ANALISIS NILAI DIDAKTIS DALAM CERITA RAKYAT PUTERA MAHKOTA LOKAN KEPULAUAN RIAU - Hani Haifzah; Dody Irawan; Ahada Wahyusari; Abdul Malik; Maulida Mustado; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the didactic values found in the folktale Putera Mahkota Lokan of the Riau Islands by Yanti Riswara. This study employs a qualitative approach using a descriptive research design. The data in this study consist of the book Cerita Rakyat Putera Mahkota Lokan Kepulauan Riau, published by the Language Center of the Ministry of National Education in 2007. The research instrument was the researcher herself, assisted by a data analysis table based on Elmubarok’s theory. The data collection techniques used included reading the book, listening, annotating, and entering data into the analysis table. The data analysis technique used was content analysis to understand, reveal, and capture the messages contained in the literary work. The results of the study show that there are fifteen didactic values, namely: (1) the value of helping others, (2) the value of empathy, (3) the value of honesty, (4) the value of sharing, (5) the value of loyalty, (6) the value of authenticity, (7) the value of wisdom, (8) the value of perseverance and tenacity, (9) the value of being helpful, (10) the value of tolerance, (11) the value of respecting others, (12) the value of patience, (13) the value of repaying evil with good, (14) the value of prioritizing good over evil, and (15) the value of the dangers of evil. These values are demonstrated through the characters’ attitudes, actions, dialogues, and conflicts. However, the value of the quality of good deeds was not found in the story. The value of the quality of good deeds refers to the way a person shows kindness to others with a sincere heart, without any hidden motives or interests. The absence of the didactic value of the quality of good deeds in this study does not indicate that Elmubarok’s theory is irrelevant to the research subject; rather, it demonstrates that a didactic value in a literary work is greatly influenced by its content, plot, conflict, character development, and the message conveyed within the work. Based on the research findings, the folktale Putera Mahkota Lokan from the Riau Islands is a literary work rich in didactic values and relevant to everyday life. These values serve not only as elements of entertainment but also as an educational tool that can serve as a guide in shaping the character and behavior of the community.